Is the wise owl wise? - Shoo Rayner (London Mind to Mind, 2010)
The tale follows Little Red Riding Hood, a young girl who sets out to visit her grandmother and bring her some treats. Along the way, she encounters a cunning wolf who tricks her and makes his way to her grandmother$1 (Bs house first. The wolf disguises himself as Grandma and tries to deceive Little Red Riding Hood. Through her cleverness and the timely arrival of a woodsman, Little Red Riding Hood and her grandmother are saved. The story highlights themes of bravery, caution, and the importance of being vigilant.s